Control y valoración de inventarios de la Contraloría Departamental del Quindío (2013)
The control and monitoring of inventories of the Comptroller General of Quindío, was held by the entity need evidence to make a decision regarding the physical inventory with the information disclosed in the financial statements of the same, in the area of fixed assets, this will start work with an analysis of the regulations of the institution on the issue of inventory, the next step was to verify human and technological resources with which the entity account, and finally worked out a physical taking inventory which resulted in several inconsistencies throw relative to the number of assets and their location, these inconsistencies by an accounting adjustment should be corrected in full for that this entity to disclose accounting information in a truthful and consistent.